Regional Development Strategies Through Educational Development in Supporting Coffee Cultivation Resilience: A Comparative Case Study of Post-Eruption Areas Between Mount Sinabung and Mount Sibayak, North Sumatera - Riah Ate Tarigan, Ruth; Setyanigrum, Sri; Sri Pasca Sari Sembiring, Desi; Tarido Sembiring, Gery; Kimpah, Jeniboy (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to analyze regional development strategies through educational development in supporting coffee cultivation resilience by comparing post-eruption areas of Mount Sinabung (active volcanic area) and Mount Sibayak (dormant volcanic area) in North Sumatra, Indonesia. The research seeks to identify the role of educational interventions in enhancing farmers’ adaptive capacity and sustainable coffee production in volcanic regions. Method: A qualitative comparative case study approach was employed, involving 40 informants comprising coffee farmers, agricultural extension workers, educational facilitators, and local government representatives from both locations. Data were collected through in-depth interviews, participatory observations, and document analysis over six months (January-June 2025). Thematic analysis was used to identify patterns and differences between the two volcanic environments. Results: Mount Sinabung post-eruption areas demonstrated 25% higher coffee productivity (Arabica: 2.0-2.8 tons/ha/year; Robusta: 2.8-3.5 tons/ha/year) compared to Mount Sibayak areas, attributed to mineral-rich volcanic soil enrichment. Educational programs showed significant impact with 85% farmer participation in sustainable practices training at Sinabung versus 65% at Sibayak. Technology adoption rates were higher at Sinabung (IoT irrigation: 50%, drone monitoring: 30%) due to intensive post-disaster educational interventions. However, Mount Sibayak areas exhibited greater long-term sustainability practices (agroforestry: 90%) due to established educational infrastructure. Novelty: This research provides the first comparative analysis of educational development impact on coffee cultivation resilience between active and dormant volcanic areas in North Sumatra. The study introduces an innovative framework linking disaster-responsive education with agricultural productivity, demonstrating how crisis-driven educational interventions can accelerate technology adoption and adaptive capacity building in volcanic agricultural systems.